Goods and Services Tax (GST) Compliance among Malaysian Consumers: The Influence of Price, Government Subsidies and Income Inequality - Sim, Choon Ling; Abdullah, Osman; Safizal, Muhammad; Sin, Kit Yeng; Lim, Yi Jin (Elsevier, 2016)
The purpose of this research is to explore the correlationbetween price, government subsidies andincome inequality towards GST compliance. Tax noncompliance remains as global phenomenon that can threaten the integrity of every tax systems hence the understanding of what people want will help to explain public dissatisfaction, heading towards the direction of developing a tax system that stimulate tax compliancein the future. Researchfindings hasrevealed that all the selected variables have significant relationship with GST compliance. To conclude, this study has bridged the knowledge in tax compliance literature, providing empirical result on potential determinants of tax non-compliancein Malaysia.